Local structure study of tellurium corrosion of nickel alloy by X-ray absorption spectroscopy. (July 2016) - Lu, Lanlu; Jia, Yanyan; Ye, Xiang-Xi; Luo, Mi; Song, Fei; Huang, Yuying; Zhou, Xingtai; Li, Zhijun; Jiang, Zheng
Graphical abstract: Highlights: Te atoms are homogeneously distributed along the surface plane direction in both grain lattice and grain boundaries (GBs) of Ni substrate after annealed at 1000 °C for 10 h. The tellurium corrosion product at 1000 °C is Ni-Te solid solution with outward relaxation of the neighboring Ni atoms around Te. The process of tellurium diffusing into nickel at high temperature is believed to be that the Ni-Te intermetallic compounds are first formed on the surface of Ni substrate then decomposed to tellurium and crystal Ni. Furthermore, tellurium diffuses into the Ni substrate and forms substitutional Ni-Te solid solution. Abstract: Clarifying the atomic structure of tellurium corrosion product in nickel alloy will help understand the mechanism of Tellurium corrosion in Molten-salt reactor (MSR). Extended X-ray absorption fine structure (EXAFS) complemented by first-principles density functional theory (DFT) calculations was used to characterize the atomic local structure of tellurium in nickel at operando temperature of 1000 °C. The investigation indicated that Te atoms diffuse into the Ni substrate to form Ni-Te solid solution with outward relaxation of the neighboring Ni atoms around Te in both grain lattice and grain boundaries (GBs). Furthermore, we propose a process of tellurium diffusing into nickel at high temperature.